Debt Costs in the Carbon Transition: The Role of Carbon Disclosure, Environmental Performance, and Profitability - Dede Yusuf Maulana; Candra Hakiki; Nani Kustina (Economics and Digital Business Review, 2026)
This research investigates how Carbon Emission Disclosure (CED), environmental performance, and profitability impact the borrowing costs of coal mining firms listed on the Indonesia Stock Exchange (IDX) between 2024 and 2025. Utilizing a quantitative explanatory design, the analysis draws on a balanced panel dataset comprising 21 firms, yielding 42 firm-year observations. The variables are operationalized as follows: CED via a disclosure index, environmental performance through the PROPER rating, profitability using Return on Assets (ROA), and borrowing costs derived from interest expenses divided by average interest-bearing liabilities. To determine the optimal estimator, the Chow, Hausman, and Lagrange Multiplier tests were applied, revealing that the Fixed Effect Model (FEM) is the most suitable. The empirical findings reveal that neither CED, environmental performance, nor profitability exert a statistically significant partial influence on borrowing costs at the 5% threshold. Furthermore, the Wald test confirms the absence of a simultaneous impact among these variables. Nevertheless, the global significance of the FEM highlights the crucial role of unobserved firm-specific traits in driving cost-of-debt variations. Ultimately, the results imply that lenders prioritize unique corporate attributes and loan agreement specifics over environmental disclosures and transient financial gains. Keywords: carbon emission disclosure; environmental performance; profitability; cost of debt; fixed effect model.